3q27.3 microdeletional syndrome: a recognisable clinical entity associating dysmorphic features, marfanoid habitus, intellectual disability and psychosis with mood disorder. Issue 1 (16th October 2013) - Thevenon, Julien; Callier, Patrick; Poquet, Hélène; Bache, Iben; Menten, Bjorn; Malan, Valérie; Cavaliere, Maria Luigia; Girod, Jean-Paul; Thauvin-Robinet, Christel; El Chehadeh, Salima; Pinoit, Jean-Michel; Huet, Frederic; et al.
Abstract : Background: Since the advent of array-CGH, numerous new microdeletional syndromes have been delineated while others remain to be described. Although 3q29 subtelomeric deletion is a well-described syndrome, there is no report on 3q interstitial deletions. Methods: We report for the first time seven patients with interstitial deletions at the 3q27.3q28 locus gathered through the Decipher database, and suggest this locus as a new microdeletional syndrome. Results: The patients shared a recognisable facial dysmorphism and marfanoid habitus, associated with psychosis and mild to severe intellectual disability (ID). Most of the patients had no delay in gross psychomotor acquisition, but had severe impaired communicative and adaptive skills. Two small regions of overlap were defined. The first one, located on the 3q27.3 locus and common to all patients, was associated with psychotic troubles and mood disorders as well as recognisable facial dysmorphism. This region comprised several candidate genes including SST, considered a candidate for the neuropsychiatric findings because of its implication in interneuronal migration and differentiation processes. A familial case with a smaller deletion allowed us to define a second region of overlap at the 3q27.3q28 locus for marfanoid habitus and severe ID. Indeed, the common morphological findings in the first four patients included skeletal features from the marfanoid spectrum: scoliosis (4/4), long and thin habitus with leanness (average Body Mass Index of 15 (18.5<N<25)) (4/4), arachnodactyly (3/4) and pectus excavatum (2/4)). This phenotype could be explained by the deletion of the AHSG gene, which encodes a secreted protein implicated in bone maturation and the TGFb signalling pathway. Conclusions: We report on a new microdeletional syndrome that associates with a recognisable facial dysmorphism and marfanoid habitus including scoliosis, neuropsychiatric disorders of the psychotic spectrum and moderate to severe ID.